Colder Ambient Temperatures Influence Acute Onset Canine Intervertebral Disc Extrusion - Barandun, Marc A.; Bult, Stella; Demierre, Stanislas; Vidondo, Beatriz; Forterre, Franck (Frontiers in Veterinary Science, 2020)
Canine intervertebral disc disease is one of the most common neurologic conditions in veterinary medicine but the influence of environmental factors thereon has not been fully investigated. Subjectively, there has been the impression of increased admissions of acute spinal cord injuries due to intervertebral disc extrusion during periods of colder temperatures. In the present retrospective study, the different weather conditions (temperature, precipitation, sunshine, humidity and atmospheric pressure) during the acute onset of clinical signs and a lag period of three days prior to the occurrence of symptoms were analyzed. One-hundred-and-one client owned dogs from the meteorological region of the Lake Geneva were presented to two referral centers during the six-year (2007-2012) study period. Chondrodystrophic dogs represented 65.3% of our population, with the French Bulldog (19.8%) and Dachshund (17.8%) being the most common breeds. Multivariable logistic regression analysis identified an increased occurrence of intervertebral disc disease during colder temperatures. Our results are congruent with those of human studies which have shown that lower ambient temperatures are associated with more pain and increased risk for muscle injuries. The interplay of endogenous (breed, anatomical characteristics) and exogenous (environmental) factors should be addressed in a larger cohort study.